New evidence and impact of electron transport non-linearities based on new perturbative inter-modulation analysis. (28th September 2017) - van Berkel, M.; Kobayashi, T.; Igami, H.; Vandersteen, G.; Hogeweij, G.M.D.; Tanaka, K.; Tamura, N.; Zwart, H.J.; Kubo, S.; Ito, S.; Tsuchiya, H.; de Baar, M.R.
Abstract: A new methodology to analyze non-linear components in perturbative transport experiments is introduced. The methodology has been experimentally validated in the Large Helical Device for the electron heat transport channel. Electron cyclotron resonance heating with different modulation frequencies by two gyrotrons has been used to directly quantify the amplitude of the non-linear component at the inter-modulation frequencies. The measurements show significant quadratic non-linear contributions and also the absence of cubic and higher order components. The non-linear component is analyzed using the Volterra series, which is the non-linear generalization of transfer functions. This allows us to study the radial distribution of the non-linearity of the plasma and to reconstruct linear profiles where the measurements were not distorted by non-linearities. The reconstructed linear profiles are significantly different from the measured profiles, demonstrating the significant impact that non-linearity can have.